Relationships between chemical composition and voluntary intake of feeds by sheep and cattle - Lambourne, L.J.; Mosi, A.K.; Butterworth, M.H. (International Livestock Centre for Africa, 1986)
Examines the relationships between chemical composition and voluntary intake of feeds (clover hay, crop residues, oat hay, snowdenia & grass hay and others) feed for sheep and cattle at ILCA HQ